Phyllostachys edulis Compounds Inhibit Palmitic Acid-Induced Monocyte Chemoattractant Protein 1 (MCP-1) Production - Higa, Jason K. (Public Library of Science, 2012)
BACKGROUND: Phyllostachys edulis Carriere (Poaceae) is a bamboo species that is part of the traditional Chinese medicine pharmacopoeia. Compounds and extracts from this species have shown potential applications towards several diseases. One of many complications found in obesity and diabetes is the link between elevated circulatory free fatty acids (FFAs) and chronic inflammation. This study aims to present a possible application of P. edulis extract in relieving inflammation caused by FFAs. Monocyte chemoattractant protein 1 (MCP-1/CCL2) is a pro-inflammatory cytokine implicated in chronic inflammation. Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and activator protein 1 (AP-1) are transcription factors activated in response to inflammatory stimuli, and upregulate pro-inflammatory cytokines such as MCP-1. This study examines the effect of P. edulis extract on cellular production of MCP-1 and on the NF-κB and AP-1 pathways in response to treatment with palmitic acid (PA), a FFA. METHODOLOGY/PRINCIPAL FINDINGS: MCP-1 protein was measured by cytometric bead assay. NF-κB and AP-1 nuclear localization was detected by colorimetric DNA-binding ELISA. Relative MCP-1 mRNA was measured by real-time quantitative PCR. Murine cells were treated with PA to induce inflammation. PA increased expression of MCP-1 mRNA and protein, and increased nuclear localization of NF-κB and AP-1. Adding bamboo extract (BEX) inhibited the effects of PA, reduced MCP-1 production, and inhibited nuclear translocation of NF-κB and AP-1 subunits. Compounds isolated from BEX inhibited MCP-1 secretion with different potencies. CONCLUSIONS/SIGNIFICANCE: PA induced MCP-1 production in murine adipose, muscle, and liver cells. BEX ameliorated PA-induced production of MCP-1 by inhibiting nuclear translocation of NF-κB and AP-1. Two O-methylated flavones were isolated from BEX with functional effects on MCP-1 production. These results may represent a possible therapeutic application of BEX and its compounds toward alleviating chronic inflammation caused by elevated circulatory FFAs.